Weak subjective–facial coherence as a possible emotional coping in older adults - Sato, Wataru; Saito, Akie (Frontiers in Psychology, 2024)
Facial expressions are critical in social interactions, particularly for older adults. Although coherence between facial expressions and subjective emotional responses has been reported extensively in young adults, there have been fewer studies on older adults. In this paper, we review a few recent studies that have reported weaker coherence between facial expressions and subjective emotional experience among older adults compared with young adults. We propose a hypothesis the subjective–facial emotional coherence may be weaker in older adults as an emotional coping.